1991
DOI: 10.1126/science.251.4995.794
|View full text |Cite
|
Sign up to set email alerts
|

The Assimilation of Elements Ingested by Marine Copepods

Abstract: The efficiency with which a variety of ingested elements (Ag, Am, C, Cd, P, S, Se, and Zn) were assimilated in marine calanoid copepods fed uniformly radiolabeled diatoms ranged from 0.9% for Am to 97.1% for Se. Assimilation efficiencies were directly related to the cytoplasmic content of the diatoms. This relation indicates that the animals obtained nearly all their nutrition from this source. The results suggest that these zooplankton, which have short gut residence times, have developed a gut lining and dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
312
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(352 citation statements)
references
References 16 publications
36
312
4
Order By: Relevance
“…The similarities between Fe and Th behavior suggest that changing the particle size spectrum and chemistry is the dominant net effect of grazing, and this process may be important for other hydrolyzed particle reactive metals, like aluminum. In studies of metazoan grazers (Reinfelder & Fisher 1991, Hutchins et al 1995, strong correlations have been found between grazer assimilation efficiency and prey subcellular partitioning of trace elements. In this study the assimilation efficiencies of protists for Fe and Th were not measured.…”
Section: Discussionmentioning
confidence: 99%
“…The similarities between Fe and Th behavior suggest that changing the particle size spectrum and chemistry is the dominant net effect of grazing, and this process may be important for other hydrolyzed particle reactive metals, like aluminum. In studies of metazoan grazers (Reinfelder & Fisher 1991, Hutchins et al 1995, strong correlations have been found between grazer assimilation efficiency and prey subcellular partitioning of trace elements. In this study the assimilation efficiencies of protists for Fe and Th were not measured.…”
Section: Discussionmentioning
confidence: 99%
“…Given the reported influence of factors such as ingestion rate (this study; Munger and Hare unpubl. data), food quality (Reinfelder and Fisher 1991;Wang and Fisher 1996), and temperature (M.-N. Croteau, INRS-Eau, unpubl. data) on metal assimilation efficiency, such differences among studies are to be expected.…”
Section: Discussionmentioning
confidence: 99%
“…In waters with relatively large zooplankton populations, the flux of fecal pellets would contribute more significantly to POC flux. C assimilation rates for ingestion and preferential loss of C from fecal pellets, result in lower C / 234 Th in larger pellets (Fisher et al, 1987;Reinfelder and Fisher, 1991;Lee and Fisher, 1992). Thus a shift from a region where flux is dominated by phytodetritus to one with higher zooplankton grazing and C export as fecal pellet material would result in a shift to lower C / 234 Th ratios.…”
Section: Regional Variations In C / 234 Thmentioning
confidence: 99%